Dabigatran for Prevention of Stroke after Embolic Stroke of Undetermined Source - Hans‐Christoph Diener; Ralph L. Sacco; J. Donald Easton; Christopher B. Granger; Richard A. Bernstein; Shinichiro Uchiyama; Jörg Kreuzer; Lisa Cronin; Otto W. Witte; Claudia Grauer; Martina Brueckmann; M. A. Chernyatina; et al. (2019)
Cryptogenic strokes constitute 20 to 30% of ischemic strokes, and most cryptogenic strokes are considered to be embolic and of undetermined source. An earlier randomized trial showed that rivaroxaban is no more effective than aspirin in preventing recurrent stroke after a presumed embolic stroke from an undetermined source. Whether dabigatran would be effective in preventing recurrent strokes after this type of stroke was unclear.